Studi Komparasi Subjective Well Being pada Siswa Pesantren Modern dan Siswa Madrasah Aliyah - Afifah Nurjannah Ismail; Whisnu Yudiana (Jurnal Psikologi Islam dan Budaya, 2020)
The objective of this study is to compare the level of subjective well-being in students who attend Islamic education, namely Modern Pesantren and Madrasah Aliyah. The two schools have differences in the form of curriculum, teaching-learning process, rules, school environment, and the relationship between students and teachers that have the potential to influence subjective well-being in students. This study used a survey approach with 79 students from Modern Pesantren and 92 Madrasah Aliyah students who were in first and second level students. Brief Adolescents’ Subjective Well-Being in School Scale was used in this research, which consists of eight items. Data were analyzed using Mann-Whitney test that showed no significant difference found on the level of subjective well-being in students attending Pesantren Modern and Madrasah Aliyah students. This result indicates that the two forms of education did not give a different effect on subjective well-being. Moreover, most of the students have subjective well-being is at a moderate level.